Identifying Green Financial Characteristics and ESG Performance: A Literature Review Study - Siska Yuli Anita; Kamsariaty; Irzan Soepriyadi; Helmi Adam; Agus Suhendra (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this literature research is expected to build hypotheses regarding the influence between variables which can later be used for further research in the scope of financial management. The literature review research article identifying green financial characteristics and ESG performance is a scientific literature article within the scope of financial management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and comes from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Capital Access affects Green Finance; 2) Digitalization affects Green Finance; 3) Capital Access affects ESG Performance; and 4) Digitalization affects ESG Performance.